2020
DOI: 10.1002/hep.31032
|View full text |Cite
|
Sign up to set email alerts
|

Patatin‐Like Phospholipase Domain‐Containing Protein 3 I148M and Liver Fat and Fibrosis Scores Predict Liver Disease Mortality in the U.S. Population

Abstract: Background and Aims Fatty liver causes premature death worldwide and requires long‐term health care. We examined relationships of liver disease markers, including patatin‐like phospholipase domain‐containing protein 3 (PNPLA3) I148M, with mortality in the U.S. National Health and Nutrition Examination Survey, 1988‐1994, with 27 years of linked mortality data. Approach and Results We studied 13,298 viral hepatitis negative adults who fasted at least 4 hours using the nonalcoholic fatty liver disease (NAFLD) liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 43 publications
(108 reference statements)
5
51
3
Order By: Relevance
“…The effect on CVD risk is less clear for PNPLA3 I148M carriers. Association studies have shown either no effect [ 29 , [42] , [43] , [44] ] or modest protection [ 34 ] from coronary artery disease (CAD) when comparing I148M carriers to non-carriers. Two studies that specifically matched for NAFLD presence (by histology or ultrasound) found no protection from CAD in I148M carriers [ 43 , 45 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The effect on CVD risk is less clear for PNPLA3 I148M carriers. Association studies have shown either no effect [ 29 , [42] , [43] , [44] ] or modest protection [ 34 ] from coronary artery disease (CAD) when comparing I148M carriers to non-carriers. Two studies that specifically matched for NAFLD presence (by histology or ultrasound) found no protection from CAD in I148M carriers [ 43 , 45 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Elevated risks of hepatic decompensation and liver‐related death were also associated with PNPLA3 I148M in a recent Italian prospective study 25 . PNPLA3 I148M was strongly associated with liver‐related death in an analysis of the US National Health and Nutrition Examination Survey with a median follow‐up of 23 years 28 . Genetic association studies have established PNPLA3 I148M as a strong genetic determinant of NAFLD in multiple populations worldwide 29‐31 .…”
Section: Identifying Targetable Pathways For Precision Medicinementioning
confidence: 99%
“…Indeed, PNPLA3 I148M may be associated with a very small reduction in the risk of ischaemic heart disease, with odds ratios of 0.98 (95% CI: 0.96, 1.00; P = 0.79) in a recent large meta‐analysis (N = 279 013) 84 and 0.96 (0.94, 0.97; P = 4 × 10 −8 ) in a recent large exome‐wide lipidomic study (N > 300 000) 85 . PNPLA3 I148M was associated with liver‐related and all‐cause mortality but not with cardiovascular mortality, in a retrospective US general population survey with median follow‐up of 23 years 28 . Circulating triglyceride and LDL cholesterol levels are reduced or unchanged in PNPLA3 I148M carriers compared with noncarriers in multiple studies 85‐88 .…”
Section: Identifying Targetable Pathways For Precision Medicinementioning
confidence: 99%
“…Improving NITs or imaging modalities for screening NAFLD/NASH and staging liver fibrosis in NASH might clarify the epidemiology and prognosis of fatty liver in patients with diabetes. Furthermore, the genetic variant PNPLA3 I148M may complement these NITs for NAFLD surveillance [ 33 , 65 ]. Improving survival in patients with NAFLD requires collaboration between hepatologists and general physicians or diabetes specialists.…”
Section: Discussionmentioning
confidence: 99%
“…In 110,761 individuals from the Danish general population and 334,691 individuals from the UK Biobank, the combination of PNPLA3, transmembrane 6, superfamily member 2 (TM6SF2) and hydroxysteroid 17-beta dehydrogenase 13 (HSD17B13) is associated with an up to 12-fold higher risk of developing cirrhosis and an up to 29-fold higher risk of developing HCC [ 64 ]. According to the U.S. National Health and Nutrition Examination Survey (NHANES), 1988–1994, with 27 years of linked mortality data, the PNPLA3 GG genotype had an 18-fold higher risk of developing liver-related mortality [ 65 ]. In previous studies, the PNPLA3 SNP did not play any role in obesity, insulin resistance, or incidence of T2D.…”
Section: The Pnpl3 Snp and Hcc- Or Liver-related Mortalitymentioning
confidence: 99%